Kam Sin Kiew and the revitalization of Cantonese Opera in Malaysia / He Shan - He, Shan (2015)
KSK Art Crew is a Cantonese opera troupe led by Kam Sin Kiew based in Kuala Lumpur. This study examined into the changing context of KSK Art Crew as Kam revitalized the Cantonese opera in effort of sustainability. Literature reveals studies by scholars looking into Chinese opera based in China and Western countries, but there is a lack of research that examines into Cantonese opera in Malaysia, brought in by the Chinese diaspora in a country where majority of population is Malay. Methods include fieldwork, participant observation, recording, analysis and interview. Results show that the change of transmission method, change of context in music accompaniment, movement, programmes and setting were inevitable in Kam’s continuous effort to revive and revitalize Cantonese opera in Malaysia.